ChemInform Abstract: Clerodendrumic Acid, a New Triterpenoid from Clerodendrum glabrum (Verbenaceae), and Antimicrobial Activities of Fractions and Constituents. Issue 9 (4th March 2014) - Masevhe, Ndivhaleni A.; Awouafack, Maurice D.; Ahmed, Aroke S.; McGaw, Lyndy J.; Eloff, Jacobus N.
Abstract isolation, characterization, antimicrobial activities and cytotoxicity